The Effects of Ongoing Physical Activity on the Lumbar Spine in Mature Athletes - Laura Maria Condur; Andreea Georgiana Sunda; Ioan Cristian Nichita; Alina Mihaela Stanigut; Oana Laura Coiciu; Mihaela Pundiche (Balneo and PRM Research Journal)
This research looks into how common and impactful degenerative lumbar disc disease (DLDD) is among older athletes. It specifically examines how being active affects the progression of this condition and its accompanying symptoms. By using a mix of clinical data, imaging tests, and health surveys, the study focused on a varied group of athletes aged 40 and older. The main findings show a clear link between the level of athletic activity and the severity of DLDD, with differences seen across various sports. Endurance athletes were found to have more cases of symptomatic lumbar disc degeneration than those who focus on strength. These results highlight the need to understand the specific risks that older athletes face, improving knowledge about the causes and development of DLDD in this group. The findings are important as they could guide clinical practices and prevention strategies, helping healthcare providers manage DLDD in ways that suit older athletes better. Overall, the study promotes a team-based approach that tackles both athletic performance and spinal health for this population, encouraging healthier aging and continued athletic involvement.